Unveiling the link between prostatitis and periodontitis - Ramanarayana Boyapati; Chakrapani Swarna; Narasimhaswamy Devulapalli; Sahitya Sanivarapu; Kishore Kumar Katuri; Lakshmikanth Kolaparthy (Wolters Kluwer Medknow Publications, 2018)
Background: One of the important tumor markers having critically important applications in every aspect of treating men with prostatic illness is prostate-specific antigen (PSA), formed by prostate acini's epithelial cells. Where prostate is affected by inflammation or malignancy, the PSA levels rise to/and above 4 ng/ml. This study analyzes the interlink between different severity of periodontitis and prostatitis by assessment of PSA antigen levels and periodontal clinical parameters. Materials and Methods: In this study, 100 chronic prostatitis patients diagnosed to also have periodontal diseases were divided into four batches on the basis of the nature of prostatitis and levels of periodontal clinical attachment. The grouping was as: group 1A - clinical attachment level (CAL) <3 mm and mild prostatitis, Group 2A - CAL ≥3 mm and mild prostatitis, and Group 1B - CAL <3 mm and moderate-to-severe prostatitis, Group 2B - CAL ≥3 mm and moderate-to-severe prostatitis. Readings of CAL, probing pocket depth, bleeding on probing, plaque index, and gingival index (PI and GI) were recorded, followed by calculation and assessment of PSA values and correlation of periodontal parameters, respectively. Results: An important and affirmative correlation (r = 0.5549, P < 0.05) was seen between PSA and CAL scores at significance level of 5%, and also between PSA and probing depths (PD) scores at 5% (r = 0.5315, P < 0.05), indicating that PSA and CAL scores, as also PSA and PD scores are mutually dependent. The similar positive correlation was seen between PSA with PI (r = 0.3231, P < 0.05) and GI (r = 0.3567, P < 0.05) scores, respectively, at 5% level of significance, which shows PSA is also mutually dependent on PI and GI scores. Conclusion: Patients with of grades, moderate-to-severe prostatitis as well as periodontitis were found having higher PSA levels. The clinical readings of periodontal parameters were significantly higher in patients with moderate-to-severe prostatitis which shows a pathological link between the above two.